Vision screening outcomes of Grade 3 children in Australia: Differences in academic achievement. (2017) - White, Sonia L.J.; Wood, Joanne M.; Black, Alexander A.; Hopkins, Shelley
Highlights: Vision is considered to be a key component in the learning process of children. 33 out of 109 Grade 3 children were borderline/unsatisfactory at vision screening. Children referred at vision screening scored lower on literacy and numeracy tests. Vision screening could thus identify children who may be at risk of underachieving. Abstract: Learning is multisensory, thus impaired vision may impact on classroom learning and subsequently, academic achievement. This research investigated the impact of impaired vision on academic achievement in a sample of 109 Grade 3 Australian children. Approximately 30% of the sample were identified as borderline or unsatisfactory by a vision screening and were referred for a full eye examination. Children who were referred at the vision screening scored significantly lower on national standardised tests of reading, grammar and punctuation, spelling and numeracy, when compared to their not referred peers. This research has important implications for teachers and eye health professionals, as the findings highlight the importance of early vision screening in identifying children who may be achieving below their potential.